Perancangan Sistem Informasi Akademik pada TK Dalilussa’adah Berbasis Web - Maman, Maman; Apdian, Donny (Infoman's, 2019)
Utilization of informatics technology in business especially in education field can reduce the potential mistake of data processing compared to manual data processing. This study aims to build information system of academic at kindergarden Dalilussa’adah Karawang. The advantage is to provide convenience in processing the value of report cards and teaching scheduling. This application is implemented with, PHP programming language, MySQL database as data storage media. Test method using black box testing with structured approach. Approach to the development of systems equipped with flow map tools, context diagrams, DFD, data dictionary, ERD, table relationships and waterfall methods that create the initial form of the system to be created and continuously tested and developed. Information system of academic at kindergarden Dalilussa’adah Karawang are still done manually, so these can cause data errors caused by human error factor. This web-based application is designed online so teachers and homers can see the teaching schedule and input student grades. The results of scheduling teaching and processing of student report cards can be viewed and processed as reports in the form of useful information for homeroom teachers and students. The results of this study are expected to answer the difficulties that are often faced by the teaching, curriculum, teachers and homeroom so that it can be much more efficient and effective. This application is also expected to be a reference for other researchers and then can develop it for further research